Polityka zakupowa państwa jako cel zamówień publicznych - Marek-Bielawska, Agnieszka (Studia Prawa Publicznego, 2024)
The article focuses on the role of state purchasing policy as the primary aim of public procurement in Poland, considering its key aspects and impact on various spheres of economic activity. It presents detailed analyses of strategic objectives, legal regulations, and implementation practices, demonstrating the complexity and signiﬁcance of this process for the way the public procurement market functions. The main research objective of the article is to understand the role that state purchasing policy plays in shaping the structure of the public procurement market and its impact on the efficiency of public expenditure and the economic development of the country. Through the analysis of empirical data and observations gathered from various sectors of the economy, the article seeks to illustrate how effective purchasing policy can support market competitiveness, fostering innovation and entrepreneurship development. The article analyzes the state purchasing policy as a key goal of public procurement, and presents its impact on the economy, competitiveness and sustainable development, emphasizing the efficiency, transparency and innovation of procedures. However, the article not only highlights the positive aspects of purchasing policy but also identiﬁes challenges associated with it. Among them are combating corruption, ensuring the transparency of processes, and promoting fair competition. The ﬁndings presented may serve as a valuable source of information for political decision-makers and practitioners involved in public procurement management, aiming to improve the Polish public procurement system in the context of changing economic and social trends on the international stage.